Doped ferrocene modified montmorillonite as well as preparation method and application thereof

By catalyzing the formation of ferrocene ions under ultraviolet light and loading them onto montmorillonite, the problem of low catalytic efficiency of ferrocene is solved, and the efficient adsorption and degradation ability of montmorillonite is achieved.

CN119897165APending Publication Date: 2025-04-29ANHUI POLYTECHNIC UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411878429.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

As a catalyst for Fenton reaction, the dispersion of ferrocene in aqueous solution is poor, resulting in low catalytic efficiency and difficult to effectively apply in the fields of adsorption and degradation materials.

Method used

By utilizing the cation-exchangeable properties of montmorillonite, the formation of ferrocene ions is catalyzed under ultraviolet light conditions and loading it onto montmorillonite through a cation exchange process to synthesize ferrocene-doped ferrocene-modified montmorillonite.

Benefits of technology

The doping efficiency of ferrocene is improved, the specific surface area and pore size of montmorillonite is increased, and its synergistic adsorption-degradation capability in adsorption and catalytic degradation materials is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119897165A_ABST
    Figure CN119897165A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of viscous mineral modification preparation, in particular to ferrocene-doped modified montmorillonite and a preparation method and application thereof.The method comprises the steps that montmorillonite serves as a preparation raw material, calcium-based montmorillonite is modified into sodium-based montmorillonite through ion exchange, then ferrocene and the sodium-based montmorillonite are sequentially added under the condition of ultraviolet irradiation, and the modified montmorillonite is prepared through a hydrothermal method; and keeping illumination, mechanically stirring, standing, centrifuging to remove supernate, washing the precipitate with deionized water, drying, grinding and sieving to obtain the ferrocene doped montmorillonite. According to the main principle of doping, ferrocene is easily excited and oxidized into positive monovalent ferrocene onium ions in an acid solution, doping is completed through an ion exchange process, and the doping efficiency is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of modified preparation of viscous minerals, and in particular to a ferrocene-doped modified montmorillonite and a preparation method and application thereof. Background Art

[0002] Montmorillonite (MMT) is a common clay mineral that is widely distributed in soil and sediments. It is abundant in nature and is the main component of bentonite. It has a 2:1 structure and is composed of repeated tiny units of aluminum oxygen octahedron and two layers of silicon oxygen tetrahedron. As a natural nanomaterial, the basic flake size of montmorillonite is tens to hundreds of nanometers wide and 1-1.8 nanometers thick. The interlayer space between adjacent structural units in montmorillonite contains hydrated cations, such as Na + , K + or Mg 2+ In addition, MMT is a clay mineral with a large amount of isomorphous substitution. The silicon-oxygen tetrahedral sheets can be 3+ or Fe 3+ substituted, while the alumina octahedral sheets are often replaced by Mg 2+ Substitution. Since the coordinated oxygen charge is not completely neutralized, the montmorillonite layers are usually negatively charged, allowing cations such as sodium and calcium to be exchanged in the interlayer region. Therefore, montmorillonite has cation exchange capacity and is widely used as a carrier for homogeneous catalysts.

[0003] The insolubility of ferrocene in water makes it poorly dispersible in aqueous solution as a catalyst for Fenton reaction, resulting in low catalytic efficiency. How to relatively easily form ferrocenium ions and load them on montmorillonite to synthesize ferrocenyl montmorillonite (Fc-MMT) for better application in the field of adsorption and degradation materials is an urgent problem to be solved. Summary of the invention

[0004] In view of this, the purpose of the present invention is to propose a ferrocene-doped modified montmorillonite and its preparation method and application, so as to utilize the "cation exchangeable" property of montmorillonite to rapidly produce ferrocenium ions through ultraviolet light catalysis, and to exchange cations with montmorillonite to finally load the ferrocenium ions onto the montmorillonite to synthesize ferrocenyl montmorillonite (ferrocene-doped modified montmorillonite), so as to facilitate better application in the field of adsorption and degradation materials.

[0005] Based on the above purpose, the present invention provides a method for preparing ferrocene-doped modified montmorillonite, comprising the following steps:

[0006] S1, adding montmorillonite to an alkali solution, stirring and cooling, separating particles smaller than 2 μm, and then washing, drying, grinding and sieving to obtain sodium montmorillonite;

[0007] S2, adding ferrocene to pure water, and stirring under ultraviolet light to obtain a blue ferrocenium ion solution;

[0008] S3, mixing sodium montmorillonite with a ferrocenium ion solution and performing a photocatalytic reaction, wherein the mass concentration of the sodium montmorillonite is 0.5-2.5%;

[0009] S4. The reaction product obtained in S3 is centrifuged, and the precipitate is washed with water, dried, ground, and sieved to obtain ferrocene-doped modified montmorillonite powder.

[0010] The alkali solution in S1 includes a NaOH solution, the concentration of the NaOH solution is 1 M, and the mass volume ratio of montmorillonite to the NaOH solution is 1 g:50 mL.

[0011] In S1, the stirring is carried out at 89-91° C. for 1.5-2.5 h, the drying is carried out at 108-112° C. for 11-13 h, and the sieving is carried out through a 200-mesh nylon sieve.

[0012] The mass volume ratio of ferrocene to pure water in S2 is 0.5 g:200 mL, and the pH value of pure water is adjusted to 3.

[0013] The stirring under the ultraviolet light condition in S2 is stirring at a rotation speed of 900 rpm for 1 hour.

[0014] The exchange capacity of the sodium montmorillonite used is 130.94 mmol / 100 g.

[0015] The photocatalytic reaction in S3 is carried out in a multi-channel photocatalytic reaction device, and the stirrer speed is 180 rpm.

[0016] The centrifuge speed used in S4 is 180 rpm.

[0017] The drying temperature in S4 is 80°C.

[0018] Optionally, the loading amount of ferrocene is 9.5-9.8%. Preferably, the loading amount of ferrocene is 9.63%.

[0019] The invention also provides a ferrocene-doped modified montmorillonite, which is prepared by the preparation method.

[0020] The invention also provides application of the ferrocene-doped modified montmorillonite in adsorption and catalytic degradation of materials.

[0021] Ferrocene is easy to form ferrocenium ions under acidic conditions of pH = 3.00. During the experiment, it was found that ferrocenium placed in an acidic solution of pH = 3.00 under ultraviolet light will accelerate the formation of ferrocenium ions. According to the calculation of VESTA software, it was found that the lattice spacing of montmorillonite is approximately The lattice spacing of ferrocene is only Therefore, it is theoretically feasible to load ferrocene onto montmorillonite. Therefore, the present invention utilizes the "cation exchangeable" property of montmorillonite to rapidly produce ferrocenium ions by ultraviolet light catalysis and exchange cations with montmorillonite, and finally successfully loads ferrocenium ions onto montmorillonite to synthesize ferrocenyl montmorillonite (Fc-MMT).

[0022] Beneficial effects of the present invention: The present invention utilizes ferrocene, which is easily excited and oxidized to positive monovalent ferrocenium ions in an acidic solution, and completes doping through an ion exchange process, thereby greatly improving the doping efficiency. The specific surface area of ​​the montmorillonite modified by Fc has increased to a certain extent, indicating that the rinsing of the alkaline solution and the presence of ferrocene are beneficial to increasing the specific surface area of ​​ferrocene. The strong oxidizing property of the alkaline solution leads to the loss of organic matter in the montmorillonite, but the pore size has increased to a certain extent after the Fc modification, which is beneficial to improving the pore size. The ferrocenyl montmorillonite (ferrocene-doped modified montmorillonite) synthesized by the present invention has a highly efficient synergistic adsorption-degradation ability. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 Schematic diagram of a multi-channel photocatalytic reaction device;

[0025] Figure 2 A flow chart is prepared for the present invention;

[0026] Figure 3 SEM-EDS images of Na-MMT, Fc-MMT, and Ca-MMT;

[0027] Figure 4 a is the X-ray diffraction pattern of Na-MMT, Fc-MMT, and Ca-MMT; Figure 4 b is the Fourier transform infrared spectra of Na-MMT, Fc-MMT, and Ca-MMT; Figure 4 c is the N2 adsorption-desorption curves of Na-MMT, Fc-MMT, and Ca-MMT; Figure 4 d is the pore size distribution curve of Na-MMT, Fc-MMT, and Ca-MMT;

[0028] Figure 5 a is the XPS spectrum of Fc-MMT; Figure 5 b is the Fe 2p spectrum of Fc-MMT; Figure 5 c is the O1s spectrum of Fc-MMT; Figure 5 d is the C1s spectrum of Fc-MMT;

[0029] Figure 6 This is a comparison chart of the adsorption and catalytic capabilities of different types of montmorillonite.

[0030] The markings in the figure are:

[0031] 1. Low temperature constant temperature bath; 2. Magnetic stirrer; 3. Reaction water tank; 4. Card slot; 5. Photocatalytic reaction tube; 6. Ultraviolet lamp; 7. Lamp stand. DETAILED DESCRIPTION

[0032] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0033] It should be noted that, unless otherwise defined, the technical terms or scientific terms used in the present invention should have the common meanings understood by persons having ordinary skills in the field to which the present invention belongs.

[0034] like Figure 1 As shown, the specific structure of the multi-channel photocatalytic reaction device refers to the contents disclosed in application number 2023223744576 and announcement number CN220940674U, which will not be repeated here.

[0035] The preparation method of the ferrocene-doped modified montmorillonite of the present invention comprises the following steps:

[0036] S1. Add 10g of raw calcium montmorillonite to NaOH solution, stir at a constant temperature of 90±1℃ for 2 hours, and then immerse the beaker in an ice bath for rapid cooling. Centrifuge the mixture to separate particles smaller than 2μm. Finally, rinse the sample repeatedly with deionized water until the chloride ion silver nitrate test is negative, dry at 110℃ for 12 hours, and grind through a 200-mesh nylon sieve to obtain sodium montmorillonite.

[0037] S2, in a multi-channel photocatalytic reaction device ( Figure 1 ) was added with 0.5 g of ferrocene into pure water, and a blue ferrocenium ion solution was obtained after mechanical stirring for 2 h under ultraviolet light conditions.

[0038] S3, sodium montmorillonite is placed in a ferrocenium ion solution through a multi-channel photocatalytic reaction device ( Figure 1 ) Reaction for 8 hours, the mass concentration of montmorillonite is 0.5%-2.5%

[0039] S4. Centrifuge the reaction product obtained in S3 in a centrifuge, remove the supernatant, rinse the precipitate with deionized water for three times, dry it at 80° C., grind it through a 200-mesh nylon sieve to obtain ferrocenyl montmorillonite powder.

[0040] Example 1

[0041] 10g of raw montmorillonite was added to 500mL of NaOH solution with a concentration of 1M, stirred at a constant temperature of 90±1℃ for 2 hours, and then the beaker was immersed in an ice bath for rapid cooling. The mixture was centrifuged to separate particles smaller than 2μm. The final sample was rinsed several times with deionized water and dried overnight at 110℃. The dried montmorillonite was ground through a 200-mesh nylon sieve to obtain sodium-based montmorillonite powder.

[0042] 200 mL of pure water was added to the quartz tube, and the pH of the pure water was adjusted to 3.00 (the pH of the solution was adjusted with HCl and NaOH), and then 0.5 g of ferrocene was added to the pure water. Figure 1 ) was stirred at 900 rpm for 1 h under ultraviolet conditions, and then 1.0 g of montmorillonite was added to the quartz tube and stirred at 900 rpm and 30°C for 8 h. After standing and settling for 30 min, the supernatant was removed by centrifugation. The precipitate was rinsed with pure water for 3 times and dried at 80°C. After drying, it was ground through a 200-mesh nylon sieve to obtain a blue ferrocenyl montmorillonite powder.

[0043] A field emission scanning electron microscope (Tescan Mira Lms, Czech Republic) was used to take scanning electron microscope images combined with mapping spectrum for morphological analysis ( Figure 3 X-ray diffractometer (Shimadzu XRD-6100, Japan) was used to study the structure of the prepared materials ( Figure 4 a). The chemical composition of the synthesized materials was analyzed by Fourier transform infrared spectroscopy (ThermoScientific Nicolet iS20, USA) ( Figure 4 b). The elemental composition was determined using X-ray photoelectron spectroscopy (ThermoScientific K-Alpha, USA). Figure 5 ).

[0044] The BET surface area and pore size distribution of the samples were measured using a fully automatic surface area and pore size analyzer (Micromeritics 3Flex, USA). Figure 4 c, d).

[0045] The morphology and element content of the prepared materials were analyzed by SEM-EDS. Figure 3As shown in the figure, Ca-MMT is a sheet-like curled structure, but there are some granular substances distributed on its surface, which may be caused by the presence of some fine milky white silicon particles in Ca-MMT. The Na-MMT synthesized by physical and chemical purification and modification has a sheet-like stacking structure with a smooth surface. The morphology of Fc-MMT after Fc modification has many irregular particles and small gaps, which may be due to the ferrocenium ion ([Cp - 2 Fe 3+ ] + The hydration radius of ) enlarges the interlayer distance. The elemental composition and standard deviation (σ(wt%)) of Fc-MMT were analyzed by EDS. The results are shown in Figure 1 The EDS spectrum of Fc-MMT reflects a large amount of Si, O, Al, Fe and a small amount of Na. The mass percentage of Fe is 7.13%. Through mapping analysis, we also see that a large amount of Fe is distributed in Fc-MMT. The above shows that ferrocenium ions are successfully loaded on montmorillonite.

[0046] like Figure 4 The diffraction peaks of the montmorillonite sample shown in a are compared with the standard card of montmorillonite (PDF#29–1499). The results show that for different types of montmorillonite XRD patterns, they exhibit four strong diffraction peaks at 2θ=7.1°, 19.9°, 35.0° and 54.0°, corresponding to the (001), (101), (107) and (0013) crystal planes of montmorillonite (PDF#29–1499), respectively, indicating that they still have the basic characteristics of montmorillonite after modification. Among them, the intensity of the diffraction characteristic peaks of all montmorillonites of Fc-MMT is somewhat weakened compared with Na-MMT, which may be due to the ferrocenium ion ([Cp -2 Fe 3+ ] + ) leads to lattice defects in the crystal structure, which destroys the crystal properties of MMT. Moreover, three new diffraction peaks are shown at 2θ=19.6°, 31.9°, and 45.4°, which correspond to the (200), (310), and (002) crystal planes of ferrocene, respectively, compared with the standard card of ferrocene (PDF#29–1711). According to the d002 reflection plane of the original Ca-MMT at 2θ=7.1°, the interlayer spacing d002 of the original Ca-MMT is calculated to be 1.22nm using the Bragg equation. The (002) crystal plane diffraction peak of the modified Fc-MMT shifts to the left and the d002 value is 1.39nm. This is because the ferrocenium ion ([Cp -2 Fe 3+ ] + ) compared to Ca 2+The Fc-MMT with a larger hydration radius was inserted into the interlayer of montmorillonite, thereby expanding the interlayer distance of montmorillonite. As the addition ratio of ferrocene:Na-MMT increased, the diffraction characteristic peak of the synthesized Fc-MMT showed a trend of gradually weakening. The reason may be that the increase in the proportion of Fc in the sample caused defects in the crystal structure.

[0047] The Fourier transform infrared spectrum shows ( Figure 4 b), in pure Fc, 1402 cm -1 The stretching vibration peak of VC-C (cyclopentadienyl) is 490 cm -1 The peaks at 3088 cm are the bending vibration peaks of C-Fe, -1 The stretching vibration peak of CH belongs to the stretching vibration peak of CH. For the Fourier transform infrared spectra of Ca-MMT, Na-MMT and Fc-MMT with different synthesis ratios, 3620cm -1 The peak at 1640 cm-1 belongs to the -OH bending vibration of Al-Si-OH. -1 The characteristic peak at belongs to the absorbed H 2 HOH bending vibration of O. 1030cm -1 The absorption band at SiO 2 The Si-O stretching vibration of the internal structure is 912cm -1 and 842cm -1 The absorption bands at 1030-1000 cm-1 correspond to the -OH bending vibrations of Al-Al-OH and Mg-Al-OH, respectively. -1 and 485-490cm -1 The peaks of Fc-MMT are stronger than those of Na-MMT, and the increase in intensity comes from the Fe-O stretching vibration of iron (hydr)oxide and the C-Fe bending vibration of the intrinsic iron species. It is worth emphasizing that the Fc-MMT spectrum has a peak at 1390-1402 cm -1 An additional peak appeared at 1390-1402cm -1 The stretching vibration peak of VC-C (macrocyclic ring) at the site becomes more and more obvious.

[0048] N 2 Adsorption-desorption isotherms and pore size distribution are important parameters for determining the adsorption performance of adsorbents. Figure 4 c shows the adsorption / desorption isotherms of nitrogen for Ca-MMT, Na-MMT and Fc-MMT. The isotherms are consistent with the adsorption / desorption isotherms with H 3 Type IV of hysteresis loop. Capillary condensation occurs at 0.40-0.95 (P / P 0), which is related to mesoporous adsorption, indicating that the adsorbent has a mesoporous structure. In addition, Figure 4 d shows the pore size distribution of the above adsorbents calculated using the Barrett-Joyner-Halenda (BJH) method. The pore size is concentrated around 5.0-22.0 nm. According to the definition of the International Union of Pure and Applied Chemistry (IUPAC), mesoporous structures exist in the three montmorillonite structures. As shown in Table 1, the surface area and pore volume parameters are listed. It can be seen that compared with the specific surface area of ​​Ca-MMT (22.57 m 2 / g), the specific surface area of ​​montmorillonite after Na modification and Fc modification has increased to a certain extent, indicating that the rinsing of alkaline solution and the presence of ferrocene are beneficial to increase the specific surface area of ​​ferrocene. The pore size has decreased compared with Ca-MMT, indicating that the strong oxidizing property of the alkaline solution leads to the loss of organic matter in montmorillonite. However, the pore size has increased to a certain extent after Fc modification, which shows that the use of Fc for modification is beneficial to improve the pore size of Na-MMT.

[0049] Table 1 Surface properties of Ca-MMT, Na-MMT, and Fc-MMT

[0050]

[0051] To further understand the reaction mechanism of iron modification, we investigated the chemical composition and elemental valence states of Fc-MMT by XPS analysis. Figure 5 As shown in a, the XPS spectrum of Fc-MMT shows peaks of Si and O, and the Fe 2p peak is observed, indicating that Fc-MMT is formed by Si, O and Fe. Figure 5 b The results of Fe 2p core level were further analyzed for the iron species in Fc-MMT. The Fe 2p core levels were observed at 724.83 eV and 711.55 eV. 1 / 2 and Fe 2p 3 / 2 The doublet peak of Fe 2p 3 / 2 The peak consisted of three peaks: iron (II) (710.09 eV), iron (III) (711.55 eV) and iron (0) (707.81 eV), indicating the presence of Fe (III) species. Therefore, the above results showed that Fc-MMT was successfully obtained using the ion exchange method.

[0052] like Figure 5 c-5d, after the C1s peak was deconvoluted, three chemical states were generated and assigned as C=O (288.72 eV), CO (286.42 eV) and CC / CH (284.80 eV), respectively. After the O1s peak was deconvoluted, four chemical states were generated and assigned as O=C (531.77 eV), OC (533.04 eV), H2 O(535.35eV) and O 2- (530.45 eV). XPS analysis showed that Fc-MMT contained abundant oxygen-containing functional groups and active sites, which could potentially enhance its MB adsorption capacity through various mechanisms, including H-bonding and π-π conjugation.

[0053] like Figure 6 Shown is a comparison chart of the adsorption catalytic capabilities of different types of montmorillonite (Ca-MMT, Na-MMT, Fc-MMT);

[0054] Experimental conditions: methylene blue concentration of 100 mg / L, reaction volume of 20 mL, different types of montmorillonite added in an amount of 10 mg / 20 mL reaction volume, total reaction volume of 20 mL, MB concentration of 100 mg / L, Fc-MMT added in an amount of 0.500 g / L. The adsorption reaction was carried out for the first 90 min, and H was added to the reaction system after 90 min. 2 O 2 , control H 2 O 2 The concentration of methylene blue was 25 mM. The solution after reaction was centrifuged and the absorbance of methylene blue was measured at 662 nm by ultraviolet spectrophotometry (Hitachi-UH5300, Japan), and the residual concentration of methylene blue was calculated. All experiments were repeated three times to ensure the accuracy of the experiment.

[0055] Experimental results: It can be seen that after the first 90 minutes of adsorption reaction, the remaining amount of methylene blue in the reaction system with different montmorillonite (Ca-MMT, Na-MMT, Fc-MMT) is 38.06%, 15.91%, and 38.59%, respectively. 2 O 2 After 150 minutes of catalytic degradation reaction, we can see that the remaining amount of methylene blue in the reaction system with different montmorillonite additions is 36.61%, 14.65%, and 2.35%, respectively. This shows that the synthesized ferrocenyl montmorillonite has a highly efficient synergistic adsorption-degradation ability.

[0056] Those skilled in the art should understand that the discussion of any of the above embodiments is only exemplary and is not intended to imply that the scope of the present invention is limited to these examples; under the concept of the present invention, the technical features in the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other changes in different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity. Any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing ferrocene-doped modified montmorillonite, characterized in that: The steps include: S1, adding montmorillonite to an alkali solution, stirring and cooling, separating particles smaller than 2 μm, and then washing, drying, grinding and sieving to obtain sodium montmorillonite; S2, adding ferrocene to pure water, and stirring under ultraviolet light to obtain a blue ferrocenium ion solution; S3, mixing sodium montmorillonite with a ferrocenium ion solution and performing a photocatalytic reaction, wherein the mass concentration of the sodium montmorillonite is 0.5-2.5%; S4. The reaction product obtained in S3 is centrifuged, and the precipitate is washed with water, dried, ground, and sieved to obtain ferrocene-doped modified montmorillonite powder.

2. The method for preparing ferrocene-doped modified montmorillonite according to claim 1, characterized in that: The alkali solution in S1 includes a NaOH solution, the concentration of the NaOH solution is 1 M, and the mass volume ratio of montmorillonite to the NaOH solution is 1 g:50 mL.

3. The method for preparing ferrocene-doped modified montmorillonite according to claim 1, characterized in that: In S1, the stirring is carried out at 89-91° C. for 1.5-2.5 h, the drying is carried out at 108-112° C. for 11-13 h, and the sieving is carried out through a 200-mesh nylon sieve.

4. The method for preparing ferrocene-doped modified montmorillonite according to claim 1, characterized in that: The mass volume ratio of ferrocene to pure water in S2 is 0.5 g:200 mL, and the pH value of pure water is adjusted to 3.

5. The method for preparing ferrocene-doped modified montmorillonite according to claim 1, characterized in that: The stirring under the ultraviolet light condition in S2 is stirring at a rotation speed of 900 rpm for 1 hour.

6. The method for preparing ferrocene-doped modified montmorillonite according to claim 1, characterized in that: The exchange capacity of the sodium montmorillonite used is 130.94 mmol / 100 g.

7. The method for preparing ferrocene-doped modified montmorillonite according to claim 1, characterized in that: The photocatalytic reaction in S3 is carried out in a multi-channel photocatalytic reaction device, and the stirrer speed is 180 rpm.

8. The method for preparing ferrocene-doped modified montmorillonite according to claim 1, characterized in that: The drying temperature in S4 is 80°C.

9. A ferrocene-doped modified montmorillonite, characterized in that: The method is prepared by any one of claims 1 to 8.

10. Use of the ferrocene-doped modified montmorillonite according to claim 9 in adsorption and catalytic degradation materials.

Citation Information

Patent Citations

  • Multi-channel photocatalytic reaction device

    CN220940674U